Challenges in the Implementation of Aral Program as Perceived by the Teachers in Zone I Schools Division of Zambales - Joyce E. Atrero; Esmen M. Cabal (Future Science / FSH-PH Publications, 2026)
Regional literacy gaps and poor international assessment scores prompted the Philippine government to establish the Academic Recovery and Accessible Learning (ARAL) Program under Republic Act 12028. This study investigated the challenges faced by teachers in implementing the ARAL Program in Zone 1, Schools Division of Zambales. Utilizing a descriptive quantitative survey design, data were gathered via purposive sampling from 129 public elementary school teachers across the districts of Sta. Cruz, Candelaria, and Masinloc. A self-developed 4-point Likert scale questionnaire assessed challenges across five structural domains. Teachers perceived the ARAL Program implementation as